Design and validation of a preterm birth risk scale with a periodontal approach - Maritza Peña Sisto; Reinaldo López Barroso (Medisan, 2023)
Introduction: The risk scale designed to estimate the probability of preterm birth with periodontal approach should be validated before its implementation in the clinical practice.